Substitution of the conceptual principles of improving the management system of strategic expenditures of an enterprise on the basis of public-private partnership: regulatory and legal aspect - Kolisnyk , H.M. (Ways to Improve Construction Efficiency, 2023)
The article is devoted to the substantiation of the conceptual foundations for the improvement of the strategic cost management system of the enterprise on the basis of public-private partnership from the standpoint of the regulatory and legal field. The justification of the possibilities of effective state regulation of business sector costs and the determination of specific objects of purposeful influence by the state and the methods of its implementation will make it possible to determine the structure of the business sector of the economy according to the criterion of the cost concentration factor. From the point of view of the enterprise, cost management is one of the most important components of the enterprise management process. It was determined that the purpose of the accounting and analytical system is the formation of information about all aspects related to the existing and future costs of the enterprise for the adoption of appropriate management decisions of a strategic nature, which are invested in the optimization of the costs of the enterprise. The process of accounting and analytical support for strategic cost management of the enterprise is presented. The principles of enterprise cost management have been clarified. It was found that the purpose of cost management is to ensure the implementation of a unified economic policy at the enterprise regarding planning, definition, analysis and control of the economic and operational activities of enterprises, ensuring the rational use of financial, labor and material and investment resources, the use of highly effective technologies, and the determination of ways to increase efficiency production by optimizing costs and strengthening control over production, etc. Differences between forward-looking indicators of future performance factors and delayed indicators of activity results are proposed. It has been proven that the effectiveness and efficiency of the mechanism of public-private partnership depends on the appropriate regulatory and legal environment, and the regulation of the mechanism of public-private partnership should be aimed at the formation of a favorable economic and management environment for the effective functioning of the country’s economy during martial law. The issue of ensuring enterprise cost accounting was considered at the legislative level. The need to implement cost management has been proven in practice. It has been proven that state regulation in the cost management system should be aimed at the constant search and identification of resource saving reserves in order to increase the efficiency of the financial and economic activities of the business sector.